The Virtue of Courage in Entrepreneurship: Engaging the Catholic Social Tradition and the Life-Cycle of the Business - Naughton, Michael J. (Business ethics quarterly, 2006)
The paper examines the problematic understanding of “risk” in entrepreneurial literature that locates courage in either the loss or gain of having or in the difficulty and hardship of the doing. We argue in this paper that what is lost in this vernacular view of courage is a deeper notion of the subjective dimension of work and the social need of society. Grounded within the Catholic social and moral tradition, we find a richer notion of courage, which in part corrects and rounds out the insufficient description of the vernacular understanding of courage in entrepreneurship. What we also find in this account of the virtues and subjective dimension of work is greater explanatory power of what happens to the entrepreneur in the work that he or she does. The end result of this analysis is a more spiritual, ethical and social understanding of entrepreneurship.